Evaluation of glyphosate tolerance and influence of plant growth stage and temperature on glyphosate efficacy in common lambsquarters (Chenopodium album L.) - DeGreeff, Randy D. (Kansas State University, 2015)
Common lambsquarters (Chenopodium album L.) is an annual broadleaf weed species that competes with more than 40 crop species around the world. A biotype of common lambsquarters in north central KS (DK) was not controlled by a glyphosate application. Plant growth stage and temperature have been related to overall glyphosate efficacy on common lambsquarters. The objectives were to determine the: 1) tolerance of two biotypes of common lambsquarters to glyphosate, 2) efficacy of glyphosate on common lambsquarters at different growth stages, and 3) efficacy of glyphosate on common lambsquarters when grown at different temperatures. Greenhouse dose-response experiments, shikimate accumulation assay, and glyphosate uptake and translocation experiments were conducted using DK biotype and a known susceptible biotype (RL) of common lambsquarters for comparison. Dose-response results indicated elevated tolerance of the DK biotype to glyphosate based on the GR₅₀ (a dose causing 50% biomass reduction) values (373 g ae/ha for RL vs. 552 g ae/ha for DK). Similarly, the DK biotype accumulated slightly less shikimate in the leaf discs compared to the RL biotype. Minimal differences were observed in ¹⁴C-glyphosate uptake and translocation between the two biotypes. Greenhouse-grown common lambsquarters were treated with glyphosate at a field dose (1x) of 840 g ae/ha when they were 5-7, 10-12, 15-17 or 19-21 cm tall. Common lambsquarters were also grown in growth chambers for 1 wk maintained at d/n temperatures of 25/15, 32.5/22.5, or 40/30 C and then treated with 0-, 0.125-, 0.25-, 0.5-, 0.75, 1.0-, and 2.0-x rates of glyphosate at 8-10 cm tall. Visual injury was recorded 1 WAT and biomass was determined 2 WAT. Common lambsquarters plants treated at 5-7 cm were more susceptible than larger plants to glyphosate. Furthermore, plants were more susceptible to glyphosate when grown under lower temperatures of 25/15 C than higher temperatures. Overall, these results suggest that the DK biotype of common lambsquarters appears to have elevated tolerance to glyphosate. Additionally, glyphosate should be applied early in the season when plants are small and temperatures are cooler for optimal control of common lambsquarters.
Keywords: Common lambsquarters (Chenopodium album L.); Glyphosate efficacy; Glyphosate tolerance; Agronomy (0285)